Pore and phase identification through nanoindentation mapping and micro-computed tomography in nanoenhanced cement. (November 2020) - Konstantopoulos, George; Koumoulos, Elias; Karatza, Anna; Charitidis, Costas
Abstract: In this work, a methodology is presented in order to assess the microstructure of Portland Cement through advanced characterisation. Nanoindentation is used to determine reduced elastic modulus and hardness, which are involved in the design of construction materials. Elemental mapping and X-ray scanning microtomography were also used to establish structure-property relations through porosity distribution and morphology as well as phase identification by nanoindentation and image analysis. The variation of carbon nanotubes (CNTs) concentration between 0.02 and 1.0 wt% demonstrated alterations in phase composition, and thus the effect of CNTs reinforcement in hydration progress was clarified. Characterisation by all techniques identified 0.5 wt% concentration as promising due to the formation of higher density hydrated phases, even though total porosity was not minimized. This fact was explained by nanoindentation as enhanced Calcium-Silicate-Hydrates connectivity in the porous network was detected. The voids of cement were filled with low stiffness hydrated gel phases as a result of enhanced hydration in the presence of CNTs.